POLITIK UANG DALAM PERSPEKTIF ETIKA ABSOLUTISME BERTINGKAT NORMAN L. GEISLER DAN KELUARAN 18:21 - Zulkifli Oddeng; Wilayanto Wilayanto (Misioner, 2021)
The rise of money politics transactions in every election event causes the Christian's ethical confusion, between involving oneself as a form of political responsibility or withdraw as an ascetic endeavour. This study aims to examine the issue of money politics from the point of view of Christian ethics by basing it on the thoughts of Norman L. Geisler regarding the ethics of graded absolutism and the concept of leader qualifications according to Exodus 18:21. The research method used was a hermeneutic study. The results showed that according to the ethics of graded absolutism, Christians could make difficult choices to do money politics as long as they remain in the corridor of obeying the higher laws, loving God more than humans, loving God more than governments, and exercising mercy more than honesty.